MSK1 promotes colorectal cancer metastasis by increasing Snail protein stability through USP5-mediated Snail deubiquitination - Keun-Seok Hong; Ki-Jun Ryu; Hyemin Kim; Minju Kim; Seung-Ho Park; Taeyoung Kim; Jung Wook Yang; Cheol Hwangbo; Kwang Dong Kim; Young-Jun Park; Jiyun Yoo (Experimental and Molecular Medicine)
Abstract Mitogen- and stress-activated protein kinase 1 (MSK1), a Ser/Thr kinase, phosphorylates nuclear proteins to increase their stability and DNA-binding affinity. Despite the role of MSK1 in promoting cancer progression in colorectal cancer (CRC), the precise molecular mechanisms remain unelucidated. Here we show that MSK1 expression induces the epithelial–mesenchymal transition (EMT) process and increases CRC cell metastasis. Furthermore, we discovered that MSK1 interacts with Snail, a key EMT regulator, and increases its stability by inhibiting ubiquitin-mediated proteasomal degradation. Importantly, MSK1 increased Snail protein stability by promoting deubiquitination rather than inhibiting its ubiquitination. Finally, we identified USP5 as an essential deubiquitinase that binds to Snail protein phosphorylated by MSK1. Based on the experimental data, in CRC, MSK1–Snail–USP5 axis can promote EMT and metastasis of CRC. Together, our findings provide potential biomarkers and novel therapeutic targets for further research in CRC.